Strategi Inovasi Menggunakan Aplikasi Grab Merchant Meteor Aquarium dalam Meningkatkan Daya Saing Wirausaha Pasar Ikan Hias - Hasyim, Hasyim; Hotma Boru Hutahaean; Situmorang, Romasi; Devima , Santia (Business and Investment Review, 2023)
To remain competitive in the market, innovation is needed. Product innovation is the result of developing new products carried out by a company or industry, whether existing or not yet. From old products that are already saturated on the market, we must innovate to replace these old products. The usefulness of research results in the future, both for program development and scientific interests, is compared to innovation strategies aimed at increasing competitiveness in the ornamental fish market. Innovation can have a positive impact on society, such as improving the quality of life, health, education and public services. The method used in this research is method. Qualitative research is research that produces results and processes descriptive data, such as interview transcripts, field notes, drawings, photos, video recordings.